Nazareth or social chaos - McNabb, Vincent, 1868-1943. (Norfolk, VA : IHS Press, 2009)
Distilling the work of Father Vincent McNabb's years of preaching in London's Hyde Park, this challenging and entertaining book examines urbanized and industrialized life. The arguments claim that urban life has a deleterious effect on nature, community, family, and the spirit and offer a challenge to "flee to the fields," seeking a life not dominated by technology and artificial schedules but by the forces of God and nature. Newly edited and annotated, this edition stands as an important work of English social criticism.
The call of Nazareth -- On rights and property -- The money muddle -- Things and tokens -- Social soundings -- Are we living on capital? -- Over-production or under-consumption? -- The farmers' food raid -- Cogs in the machine -- Facts for Whitehall -- Is patriotism dead? -- The sins of avarice -- Memento mei -- Dear Mother Earth -- Towards hope -- Nature's call to work and thrift -- Absenteeism -- Mass-production in agriculture -- Group home-colonisation -- Fifteen things a distributist may do.
Includes bibliographical references.
Originally published: London : Burns, Oates & Washbourne, [1933].
Description based on print version record.
Keywords: Economics -- Religious aspects -- Catholic Church; Agriculture -- Religious aspects -- Catholic Church; Christian sociology -- Catholic Church; Religion; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Electronic books